Bootstrapping IoT Provisioning with PoMA - Gutierrez, Lucas (2026)
The proliferation of Internet of Things (IoT) devices across diverse environments demands a robust, user-friendly, and efficient deployment strategy. Conventional setup methods typically involve complex, multi-step procedures that require specialized tools or technical expertise, increasing deployment time, operational costs, and the likelihood of human error. This paper introduces PoMA (Poor Man’s API), a lightweight protocol and accompanying library designed to simplify and accelerate the on-site configuration and initial connection of IoT devices. PoMA relies on three core commands and can operate over localized temporary wireless links—such as Bluetooth Low Energy or temporary Wi-Fi access points—or through Short Messaging Service (SMS). Each communication channel can be configured to different security levels based on the deployment scenario. The proposed solution provides a standardized, simple, and secure foundation for rapid IoT field installation. rapid IoT field installation.